Peran Mediasi Sistem Kerja pada Kepemimpinan dan Budaya Organisasi dalam Implementasi Nilai Berakhlak di BPS - Alifaldo Daffa Darmawan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research seeks to analyze the implementation of BerAKHLAK (Service-Oriented, Accountable, Competent, Harmonious, Loyal, Adaptive, and Collaborative) values within the Statistics Indonesia/Badan Pusat Statistik (BPS), while also investigating its impact on organizational culture via leadership and work system mechanisms. Utilizing Structural Equation Modeling-Partial Least Square (SEM-PLS), this research draws upon secondary data gleaned from